Packaging and Marketing Training for Products of Waste Processing Sites in Mangrove Tourism Area, West Oesapa Village, Kupang City - Fanggidae, Jappy Parlindungan; Nino, Indawati Jauhar; Manafe, Janri Delastriani; Setyorini, Tuti; Dioh, Septia Sakalini; Kefi, Darwin Yopie; Latupeirissa, David Samuel; Tarigan, Surya Setiadi; Sanga, Marianus Hendrilensio; Dima, Rohani Purnamasari (Edumedia Solution, 2025)
This community service activity aims to improve the skills of the 3R Waste Management Site (Recycle, Reuse, Reduce) management group in the mangrove ecotourism area of Oesapa Beach, Kupang, NTT. This TPS was built through collaboration between the government and local communities, aiming to manage waste and support economic improvement through organic fertilizer production. However, there are obstacles in the marketing of these organic fertilizers, including unattractive packaging and limited sales points in tourist areas. This service method consists of several stages: preparation, implementation, evaluation, and reporting. At the preparation stage, partner problems are identified. The implementation stage includes training on packaging fertilizer products that are neater and more attractive and marketing strategies in tourist areas, which are delivered through workshops and hands-on practice. The evaluation was carried out by comparing the condition of the partners before and after the training. The results of the activity showed an increase in skills in product packaging and the ability to design more effective marketing strategies, which can be seen from the increase in consumer interest in organic fertilizer products. The positive impact of this activity is expected to support the sustainability of the 3R TPS management group's business and contribute to environmental and economic preservation of the local community through more optimal waste management.